Exploring Parental Attachment and Optimism among 12th Grade Vocational High School Students - Izzati, Shofia Nur; Priyatama, Aditya Nanda (Universitas Negeri Surabaya, 2025)
Background: Statistics Indonesia has recorded that vocational high school graduates have had the highest Open Unemployment Rate (OUR) since 2022. This situation poses a challenge for final-year students, making it important to maintain optimism. Parental attachment can serve as a factor in shaping individual optimism. Objective: Understanding the relationship between Parental Attachment and optimism in final-year vocational high school students. Method: Quantitative research with a correlational design using Pearson Product Moment analysis. Respondents were 290 twelfth-grade students from a school in Surakarta, selected using cluster random sampling. The instruments used were the Life Oriented Test-Revised (r = 0.715) and the Parental Attachment Scale (r = 0.948). Results: There is a relationship between parental attachment and optimism in students (r=0.231; p<0.05), although the relationship is considered low. The study found differences in parental attachment scores between male and female students (Mdifference=11.341, p<0.05). Conclusion: The higher the parental attachment, the higher the students’ optimism. Future research can enrich the sample size, examine gender disparities, and explore internal factors related to optimism. Abstrak Latar Belakang: Badan Pusat Statistik mencatat lulusan SMK berada pada posisi tertinggi Tingkat Pengangguran Terbuka (TPT) sejak 2022. Kondisi ini menjadi tantangan bagi siswa tingkat akhir yang sedang menjalani masa transisi kehidupan, sehingga penting untuk memiliki optimisme. Kelekatan orang tua mampu menjadi faktor pembentuk optimisme individu. Tujuan: Mengetahui hubungan antara kelekatan orang tua dengan optimisme pada siswa tingkat akhir SMK. Metode: Penelitian kuantitatif dengan desain korelasional menggunakan teknik analisis Pearson Product Moment. Subjek adalah 290 siswa kelas 12 (NLaki-laki=272; NPerempuan=18) salah satu SMK di Surakarta dengan metode cluster random sampling. Optimisme diukur dengan Skala Life Oriented Test-Revised (r = 0.715) dan kelekatan orang tua diukur dengan Skala Kelekatan Orang Tua (r = 0.948). Hasil: Terdapat hubungan signifikan antara kelekatan orang tua dengan optimisme pada siswa (r=0.231; p<0.05) namun hubungan tergolong rendah. Hasil penelitian juga menemukan perbedaan nilai kelekatan orang tua siswa laki-laki dan perempuan (Mdifference=11.341, p<0.05) Simpulan: Hasilnya semakin tinggi kelekatan orang tua, semakin tinggi optimisme siswa. Penelitian selanjutnya dapat memperkaya jumlah sampel, melihat ketimpangan jenis kelamin, serta mengeksplorasi faktor internal yang berhubungan dengan optimisme.